Service specific expectations and evaluations of customers : a study on Turkish Airlines frequent flyer customers - Özkan, Çiğdem (My University, 1995)
unknown
Keywords: Genel yönetim; TÜKETİCİ DAVRANIŞI-HAVA İŞLET; Yürütmenin yönetimi